2009
DOI: 10.1007/s00586-009-1216-1
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic vertebral osteomyelitis: identification of microorganism and laboratory markers used to predict clinical outcome

Abstract: The aim of this study is to determine the predictive values of laboratory indicators of pyogenic vertebral osteomyelitis (PVO) and a potential cure if the microorganism cannot be identified. Forty-five consecutive patients with PVO were enrolled. Antibiotic therapy with or without surgery was performed according to microorganism. In the negative-culture (NC) group, cefazolin was administered in cases of hematogenous PVO, and vancomycin was administered in cases of postoperative or procedure-related PVO. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
4
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 34 publications
(60 reference statements)
6
93
4
8
Order By: Relevance
“…Generally, most patients were older men, experienced pain and had fever, and one-third of patients had neurological complications, confirming previous findings 14,16,17 . Spinal infection was most frequently located in the lumbar spine and usually affected two neighboring vertebrae and intervening disc, which is similar to other previously conducted studies 2,5 .…”
Section: Discussionsupporting
confidence: 87%
“…Generally, most patients were older men, experienced pain and had fever, and one-third of patients had neurological complications, confirming previous findings 14,16,17 . Spinal infection was most frequently located in the lumbar spine and usually affected two neighboring vertebrae and intervening disc, which is similar to other previously conducted studies 2,5 .…”
Section: Discussionsupporting
confidence: 87%
“…When the bacteria is not identified we use cloxacillin alone or associated with other antibiotics. Recent studies have found no significant differences in relation to treatment outcome between patients with or without a microbiological diagnosis [25], although it is a worldwide rule that, whenever possible, therapy must be instituted with intravenous antibiotics based on cultures and bacterial sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Yoon [56] reassuringly lets us learn that although one should strive to find the infecting organism, which they only identify it in 75% of cases, patients can be treated successfully with what they describe as ''antibiotics selected according to etiological setting'', which in their case were cefazolin or vancomycin, and the values of CRP and ESR were reliable guides of successful recovery.…”
Section: Spine Infectionmentioning
confidence: 99%